PENGARUH HARGA TERHADAP VOLUME PENJUALAN MIE INSTAN GORENG PADA MINIMARKET INDOMARET MANISREJO DI KOTA MADIUN - Adrianus Widya Kristianto (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
In general,  the high  and low price  of a commodity  is very important  for a trading company in selling the products so increasing  its sales volume. Price is one ele- ment of a marketing  strategy is used as a benchmark  for consumers  to obtain goods or services, so as to achieve the objectives of the company  (at a profit).While  sales volume is all of the  sales result  that can be achieved  by a company  and  can be measured  by specific units. Usually the lower price of product  it can increase sales volume, while high price of product  will resulting  in decreased  sales volume. But in fact the consumers  is often assume the price is the determining factor of a product  quality, high price goods is generally considered  to have better quality  than the goods whose have  low prices. The method used in the research is quantitative,  the research conducted  at Minimarket  espe- cially in Indomaret Manisrejo Madiun city. The data obtained from the documentation  of the closing monthly  data of Indomaret Manisrejo  in Madiun which are contain list price and sales volume.  The result  of analysis  data obtained  in this research using regression correlation  test, F test, and t test. In correlation values obtained rhit <= rtable (0,396 <= 0,444) or sig(hit) > = sig(prob) (0,84 >= 0,05), so we can conclude that H, is accepted it means there is no relationship   between   the price  of the  fried  instant   noodle  sales  volume  in minimarket Indomaret   Manisrejo   in Madiun  city. Fisher's   test values  obtained  in Fbit< Flabe(l3,339  < 4,414) or sighil > sigprob(0,84  > 0,05).  So we  can conclude  that Ho is accepted   its means that no price impact  on the sales volume  of instant  fried noodle  on minimarket   Indomaret Manisrejo in Madiun.  While  in regression coefficient test / test t values  obtained  thit< ttabel (-1,827  < 0,842)  or  values  sighit > sigprob (0,84  > 0,05), it can  be  concluded   that  H, is accepted,   it means  that  there  is no difference  price  to price  effect  of sales  volume   fried instant  noodle  on minimarket   Indomaret   Manisrejo   in Madiun.